[tex]x^2 + y^2 + 7x - 16y + 4 = 0\\x^2+7x+y^2-16y+4=0\\x^2+2\cdot 3,5\cdot x+3,5^2-3,5^2+y^2-2\cdot 8\cdot y+8^2-8^2+4=0\\(x+3,5)^2-3,5^2+(y-8)^2-8^2+4=0\\(x+3,5)^2+(y-8)^2-12,25-64+4=0\\(x+3,5)^2+(y-8)^2=72,25\\C(-3,5;8)[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
[tex]x^2 + y^2 + 7x - 16y + 4 = 0\\x^2+7x+y^2-16y+4=0\\x^2+2\cdot 3,5\cdot x+3,5^2-3,5^2+y^2-2\cdot 8\cdot y+8^2-8^2+4=0\\(x+3,5)^2-3,5^2+(y-8)^2-8^2+4=0\\(x+3,5)^2+(y-8)^2-12,25-64+4=0\\(x+3,5)^2+(y-8)^2=72,25\\C(-3,5;8)[/tex]